مدى فاعلية نظم المعلومات المحاسبية في المصارف التجارية الليبية في تلبية متطلبات عملية الرقابة " دراسة حالة بمصرف التجارة والتنمية " (Economic studies journal, 2022)
The study dealt with the subject of the effectiveness of accounting information systems in Libyan commercial banks in meeting the requirements of the control process "a case study of the Bank of Commerce and Development." Oversight, where (70) questionnaires were distributed, of whom (59) were valid for statistical analysis, i.e. 84.3% of the total distributed questionnaires, which is a percentage that is subject to statistical analysis.The study concluded that the accounting information systems in the bank provide additional information (analytical lists, statistical tables, graphs, ..) that helps the management to make comparisons and better evaluate performance in the bank, and the information provided by the accountants contributes to the technical challenges of the bank. Negative deviations from the budget and taking corrective measures in this regard. The information provided by the accounting reports in the bank contributes directly to setting control procedures and internal control. The accounting information helps in following up on the effectiveness of the decisions taken in the bank and provides control reports appropriate to the different levels of management enabling the performance of the various levels in a timely manner. To take corrective measures and decisions in this regard.The study recommended the need to work on holding training courses for employees and for all disciplines and in various departments in the field of accounting information systems in order to increase their ability to develop those systems, as well as work on developing general controls for accounting information systems as a result of the development of banking services providedـ